Water, sanitation, and hygiene insecurity and disease prevention behaviors during the COVID-19 pandemic in low-income neighborhoods of Beira, Mozambique. - Rebecca S Kann; Jedidiah S Snyder; Courtney Victor; Zaida A Cumbe; Joshua V Garn; Sandy McGunegill; Rassul Nalá; Matthew C Freeman; Karen Levy (PLoS ONE)
Background Inadequate water, sanitation, and hygiene (WASH) are important drivers of the global burden of disease, and their impact is exacerbated during outbreaks. Directives to practice handwashing and physical distancing may be impractical for people that have limited access to WASH resources. In this study, which took place during the acute phase of the COVID-19 pandemic, we explore the relationship between control measures for global health crises and water, sanitation, and hygiene insecurity, with implications for other infectious diseases and future health emergencies. Methods We investigated the relationship between WASH-related factors and disease prevention behaviors (handwashing, physical distancing, and masking), and the role of demographic characteristics and risk perceptions in influencing these relationships in low-income neighborhoods of Beira, Mozambique during the COVID-19 pandemic. We utilized data collected from 1,762 randomly selected households during a population-based survey. We fit multivariable logistic regression models to examine the associations between various WASH factors and disease prevention outcomes of interest, adjusting for individual- and household-level demographic characteristics and risk perceptions. Results Over 98% of people had access to improved drinking water and over 80% of people had access to improved sanitation facilities. There was a high level of reported adherence to handwashing (95.5%) and physical distancing (91.7%) practices during the COVID-19 pandemic. There was a lower odds of reported handwashing [aOR = 0.89; 95% CI: 0.81, 0.98] and physical distancing [0.85 (0.80, 0.92)] among respondents who had higher levels of water insecurity. Respondents that had a water source in their dwelling had a higher odds of reporting of physical distancing [2.03 (1.22, 3.41)] compared to people that had to leave their household to access water. There was a higher odds of reported handwashing and physical distancing among respondents who had their own sanitation facility, compared to a shared one [handwashing: 2.77 (1.35, 5.82); distancing: 1.61 (0.95, 2.73)], and those that had a sanitation facility inside their compound compared to outside their compound [handwashing: 2.11 (0.75, 5.71); distancing: 1.50 (0.65, 3.36)]. Respondents with a basic handwashing station, compared to no facility or a limited facility, had a higher odds of reported handwashing [4.45 (2.37, 8.65)], and those that had a connected handwashing station, compared to an unconnected handwashing station, had a higher odds of reporting handwashing and physical distancing [handwashing: 2.13 (0.68, 8.54); distancing: 1.77 (0.77, 4.53)]. Conclusions Despite a high level of knowledge about the risks posed by COVID-19 and understanding of the benefits of handwashing and physical distancing, limitations in access to water, sanitation, and hygiene infrastructure acted as a barrier to people practicing disease prevention behaviors during the COVID-19 pandemic.